Description of Hypertension Prevention in Puguh Village, Boja District, Kendal Regency - Aprilia, Nadhia Wahyu; Nugroho, Bayu Yoni Setyo (PROMOTOR, 2025)
This study aims to identify the epidemiological characteristics of people with hypertension in Puguh Village, Kendal Regency during the third quarter of 2024. Using a descriptive research design with a population of 110 respondents, data was collected using Kobotoolbox and analyzed using statistical software. The results show that the majority of respondents were female (73.6%), aged 31-90 years (87.3%), had elementary school education (48.2%), and worked in the informal sector (46.4%). Respondents' knowledge level about hypertension was fairly good, with 94.5% understanding the term hypertension and 98.2% being aware of its risks for heart disease and stroke. However, knowledge about risk factors such as smoking remained low (34.5%). Regarding attitudes, 90.9% of respondents agreed on the importance of regular blood pressure checks, and 92.7% supported regular physical activity. An area still needing attention is the understanding of the relationship between obesity and hypertension, where only 51.9% of respondents understood the correlation. This study recommends strengthening education about lifestyle modification risk factors, developing specific educational programs about the dangers of smoking, and implementing more innovative educational media to improve the community's comprehensive understanding of hypertension.